PKM PEMBERDAYAAN KADER DAN BIDAN DESA PEREAN KANGIN UNTUK MENINGKATKAN GERAKAN SADARI KANKER PAYUDARA - Analysa Analysa; Desak Putu Oki Lestari; I Gusti Alit Artha (JURNAL SEWAKA BHAKTI, 2023)
In 2021 there were 10 breast cases from the Baturiti sub-district which carried out examinations in the PA laboratory at Tabanan Hospital. 6 of them (60%) turned out to be cases of malignancy, and 4 of them (66.66%) stage III and IV which are the final stages of breast cancer. Perean Kangin Village which is one of the villages in the Baturiti sub-district with the most cases of breast tumors. The long-lasting pandemic has contributed to the decreased activity of cadres and increased delays in breast cancer screening. If the patient can be detected early and get treatment as soon as possible, it will give hope for recovery and a better life expectancy. One of the early detection of breast cancer is breast self-examination (BSE). It is hoped that re-activating midwives and village cadres will motivate the community to do BSE. The result of this PKM was an increase in the knowledge and attitude of cadres towards BSE. We also provide investment goods in the form of digital baby and adult weight measuring devices, stunting mats and height measuring devices for early detection of health problems.